Spin-coated Cu2nisns4 Thin Films: The Impact Of Thiourea’s Molar Concentration - Rashid, M M; Noman, A A; Islam, S; Ahmed, F; Bashar, M S; Jamil, A T M K; Ahmed, S J (Bangladesh Journal of Physics, 2025)
Copper-Nickel-Tin-Sulfide, Cu2NiSnS4 (CNTS) thin films are deposited on to glass substrates through simple and cost-effective spin coating technique, with the variations in the molar concentration of thiourea (MCT). In this research, CuCl2.2H2O, NiCl2.6H2O, SnCl2.2H2O and SC(NH2)2 are utilized as the sources of copper, nickel, tin, and sulfur ions, respectively. The influence of MCT on the structural, morphological, and optical properties of the CNTS thin films have been investigated. The XRD results reveal that all CNTS thin films exhibit a cubic crystalline structure and a preferential orientation along the (111) plane. The mean crystallite size for the intense peak (111) is found to enhance from 7.24 to 10.81 nm with MCT. Conversely, the dislocation density and microstrain are found to decrease from to and to , respectively. The density and surface roughness of the films are also found to increase with MCT. The absorption coefficient (on the order of ), refractive index, extinction coefficient, dielectric constant, and optical conductivity all increased, while the percentage transmittance and optical band gap decreased with MCT. These outcomes suggest that CNTS thin film could a promising material for the use as an absorbing layer in photovoltaic applications and optoelectronic devices. Bangladesh Journal of Physics, 28(1), 39-50, June 2021